(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Fashion store design significantly contributes to tourism by creating immersive and culturally resonant retail environments. Through visual merchandising, architectural innovation, sensory engagement, and cultural storytelling, fashion retail enhances destination branding while offering memorable experiences for both local and international visitors. Well designed retail spaces serve as more than just points of sale; they become tourist destinations, offering unique atmospheres that reflect the brand’s identity while harmonizing with the cultural and architectural character of the location. For instance, flagship stores in global cities such as Tokyo, Paris, and Milan integrate innovative layouts, cutting edge technology, and localized cultural elements, transforming shopping into a leisure and tourism activity. Strategic design features such as open plan interiors, interactive displays, and photogenic corners encourage visitors to engage with the space, share their experiences on social media, and, in turn, promote the destination globally . Moreover, integrating local art, heritage, and sustainable materials within the store design not only appeals to experience seeking travelers but also strengthens the narrative of place making, aligning fashion retail with cultural and creative tourism trends. As shopping tourism continues to expand, innovative and aesthetically compelling store designs have become critical in differentiating destinations and enhancing their global appeal. Fashion store design plays a critical role in shaping tourism by creating immersive and culturally resonant retail environments. This study employs a qualitative-descriptive approach to investigate how visual merchandising, architectural features, sensory engagement, and cultural storytelling in fashion retail influence tourist attraction and destination branding. Data were collected through case studies of selected fashion stores, in-depth field observations, and analysis of secondary documents such as design reports and promotional materials. The findings reveal that innovative spatial layouts, thematic displays, and integration of local cultural narratives not only enhance tourists’ retail experiences but also contribute to the identity and competitiveness of destinations. This research highlights the significance of fashion retail as a driver of cultural tourism and suggests that store design can function as both a commercial and cultural platform.